تعليم الخط العربي عن بعد بجمعية دار الخط من خلال منهج "حميدي" أثتاء الوباء - Faris Maturedy; Ahmad Yasir Amrulloh (Journal of Calligraphy, 2021)
The Covid-19 epidemic has spread around the world. As a result, people's activities stopped especially educational activities in schools. This is the case with the teaching of calligraphy using the "Hamidi" curriculum in Dar Al-Khatt. The aim of the research is to describe the process of teaching calligraphy with a "Hamidy" approach during the epidemic. Then the researchers used the qualitative research method. Thus, the data was collected by a deep interview with the calligraphy teacher at the Dar Al-Khatt Society. The data was analyzed by the descriptive method. The result indicated that learning the script takes place either directly or indirectly from a distance. After it was a direct meeting between the teacher and students. The teacher complained of their inability to provide suggestions and correction accurately.